Study on the degradation of accumulated bisphenol S and regeneration of magnetic sludge-derived biochar upon microwave irritation in the presence of hydrogen peroxide for application in integrated process. (December 2019) - Lv, Ying; Zhang, Jingyi; Asgodom, Michael Engda; Liu, Dingyi; Xie, Huifang; Qu, Hongxia
Graphical abstract: Highlights: Magnetic sludge-derived biochar offer the feasibility of an integrated process. Ethanol-water system decouples the adsorption and degradation. ·OH and h + are the main active radicals involved in reactions. Degradation and regeneration can be obtained in MW + H2 O2 under certain conditions. Abstract: Based on the multi-functional magnetic sludge-derived biochar (MSBC), an innovative integrated process–coupling accumulation by adsorbing, degradation by microwave (MW)-induced catalytic oxidation in the presence of H2 O2 and the regeneration of adsorbent simultaneously, was proposed. In this study, bisphenol S (4, 4′-sulfonyldiphenol) was chosen as the pollutant model, its behaviors and related mechanism of BPS and MSBC in MW + H2 O2 system were investigated. The BPS effective degradation on MSBC was proved by decoupling the adsorption and degradation with solvent extraction. OH and h + play vital roles based on the scavenger tests. The synergistic effects of hot-spot of microwave irradiation, activation of H2 O2, and charge transfer-induced doping effects of MSBC were attributed to the reactions. This work proves the feasibility in economics and energy-save treatment approach for low concentration organic pollutants in water.